TINJAUAN HUKUM EKONOMI ISLAM TERHADAP PEMANFAATAN GADAI KEBUN KARET (Program Studi Muamalah Fakultas Syariah dan Hukum, 2022)
ABSTRACT The use of rubber as the object of pawning is a common thing in society, the refore it is important to study it in depth if examined through a review of Islamic economic law. That is why this research was conducted with the aim of providing a description of the Islamic economic law review on the use of pawn rubber plantations, especially in Modong Village, Tanah Abang District, Penukal Abab Lematang Ilir Regency (PALI). This research respondents were determined by the researchers with the criteria as the giver and recipient of the pawn. The results obtained from the research conducted stated that the practice of using rubber plantations as the object of pawning in Modong Village had been going well, because there had been an agreement between the giver and the recipient of the pawn as determined when the pawn agreement occurred. Another thing that can be seen is the use of rubber plantations which are the object of the pawn, which is fully owned by the pawnee (murtahin). Judging from Islamic economic law, the use of rubber plantations as an object of pawning in Modong Village is partly in accordace with Islamic law because most of the pawn contracts that have been carried out have stated that the pawnbroker gave permission to use the proceeds from the pawned rubber plantation. Another thing that is inconsistent or contrary to Islamic law is related to the arrangement to use the object of the pawn proportionally, namely in accordance with the costs incurred to maintain the object of the pawn, but what happened in the village of Modong was that all the benefits of the pawned rubber plantation were received by the recipient of the pawn. Keywords: Islamic Economic Law, Pawn, Rubber Plantation